Making History : A Novel - Fry, Stephen, 1957- (London Arrow, 2011)
What if Hitler had never been born? An unquestionable improvement, one would reason - and so an earnest history grad student and an aging German physicist idealistically undertake to bring this about by preventing Adolf's conception. And with their success is launched a brave new world that is in some ways better than ours - but in most ways even worse.
Include Index
Keywords: Hitler, Adolf, 1889-1945 -- Germany -- Time Travel